The Tug-of-War Over Truth: A Foucauldian Case Study on the Interplay of Competing Discourses in Education - Rose, Patrick Allen (Frontiers in Education, 2022)
The present study applies a Foucauldian critical analytic to investigate competing discourses in education that are shown to be present in one public high school in the southern part of the United States. It is revealed how these discourses intersect and collide with each other to reinforce certain values, principles and practices, but eventually loosely coalesce along with other social interactions into general rules and social norms within the high school. It is found that technology itself rep-resents a separate competing discourse with its own set of unique truths, goals, language and tools that both overlap and challenge other dominant discourses. Foucault’s concepts about power and governmentality provide the deductive design for data interpretation. Teacher and school administrator retellings are examined for signs of structures of thought and discursive truths that characterize ways of thinking that represent opposing points of views about the role of technology in education and its effect on defining the ‘right’ way to teach. A framework is proposed for under-standing and comparing the discourses based on their differing views of technology.